STRATEGI IMPLEMENTASI PENDIDIKAN QUR'ANI - Rosnidarwati Rosnidarwati; Restu Andrian (Pedagogik : Jurnal Ilmiah Pendidikan dan Pembelajaran Fakultas Tarbiyah Universitas Muhammadiyah Aceh, 2019)
The education in the Islamic studies is the discussion period about at-tarbiyah, al-ta'lÄ«m and al-ta'dÄ«b. The term are popularly used in Islamic education is at-tarbiyah. The creation of Qur'ani education goals is a great effort for humans to prepare the provisions of the life of the world and the hereafter while completing physical and spiritual balance as a complete container for oneself. The personality that is the target of Islamic education is "a kaffah Muslim personality. The teacher has an important role in counteracting the formation of character that is not commendable among students. In the national education system, the law must mandate the purpose of education so that students become human believers and fearful. The Qur'anic method of education that can be applied to students is the method of habituation, the method of á¸¤iwÄr, the Method of Targhib and Tarhib (Reward and Funishment), the method of victory (story), the amthÄl Method (Imagery or Metaphor), Â and Mauizah Method.Key Word: Implementation, Education, Qur'ani